The Influence of Harvested Land Area, Labor, and Working Capital on Rice Production in Penebel District, Tabanan Regency - Ni Gusti Ayu Dwi Widyari; Sudarsana Arka (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The agricultural sector, particularly the food crop subsector namely rice plays a crucial role in the regional economy, especially in ensuring the supply of staple food. Tabanan Regency, located in Bali Province, is widely recognized as the